A Prospective Study of Fractionated Dual‐Wavelength Picosecond Laser in Treating Acne Scar - Yang, Ching‐Sheng; Huang, Yau‐Li; Cheng, Chun‐Yu; Hu, Sindy; Chang, Shyue‐Luen; Lee, Mei‐Ching (Lasers in surgery and medicine, 2020)
Background and Objectives The picosecond (PICO) laser has been a new and promising device. But, so far, there have not been many prospective studies investigating the efficacy in acne scar treatment. This study evaluated the efficacy and safety of the dual‐wavelength picosecond laser in the treatment of acne scar. Study Design/Materials and Methods A total of 20 patients with skin type III–IV were enrolled in this study. Eighteen patients completed the study. All patients completed six treatment sessions within a 1‐month interval. All patients were treated using both 532 and 1,064 nm fractionated dual‐wavelength picosecond handpieces. In evaluation, Goodman and Baron's quantitative global acne scarring grading system (GSS) was scored by two physicians. Patients also judged the results themselves by Visual Analog Scale (VAS) and pain score. Results The average baseline score of GSS quantity and quality were 15.22 and 3.00, respectively. The final scores were 10.61 and 2.33. The average baseline of patient VAS score was 4.28. The final score was 2.00. All scores achieved statistical significance (P < 0.05). No serious long‐term side effects were recorded. Conclusion Acne scar treatment with the fractionated dual‐wavelength picosecond laser has shown both efficacy and safety in this study. Lasers Surg. Med. © 2020 Wiley Periodicals, Inc.